1980
DOI: 10.2307/3898577
|View full text |Cite
|
Sign up to set email alerts
|

Diet Selection by Cattle under High-Intensity Low-Frequency, Short Duration, and Merrill Grazing Systems

Abstract: A study was conducted to evaluate standing crop of forage and cattle diets for a 'I-pasture high-intensity low-frequency (HILF) grazing system, and a 'I-pasture short-duration grazing (SDG) system on the same area. A epasture, 3-herd (Merrill) deferred rotation grazing system was sampled as a standard for comparison. Standing crop of forage was highest for the HILF grazing system compared to the SDG and Merrill grazing systems. The Merrill system with brush control (Pasture 10) had a greater standing crop than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1
2

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 6 publications
4
20
1
2
Order By: Relevance
“…3). Other studies (Taylor et al 1980, McGinty et al 1983) also confirm the relative preferences for forage classes estimated for cattle in this study.…”
Section: Comparisons With Published Datasupporting
confidence: 89%
“…3). Other studies (Taylor et al 1980, McGinty et al 1983) also confirm the relative preferences for forage classes estimated for cattle in this study.…”
Section: Comparisons With Published Datasupporting
confidence: 89%
“…Diet quality, in the fourth year of grazing, was similar under SDG and CG, indicating that SDG did not increase or decrease forage quality. Taylor et al (1980) reported similar results from SDG and Merrill systems when dietary crude protein and digestible organic matter were determined. This further indicates that decreases in animal performance were related to stocking rate and ultimately forage ability.…”
Section: Discussionmentioning
confidence: 55%
“…Other studies have reported that livestock and wildlife often consume prickly pear even when forage quantity is not limited (Taylor et al 1980, Fontenot et al 1991). …”
Section: Prickly Pear Intakementioning
confidence: 99%